2015
DOI: 10.1080/09540121.2015.1090535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoking and nicotine dependence on adherence to antiretroviral therapy among HIV-positive patients in Vietnam

Abstract: Cigarette smoking is increasingly recognized as an indicator for inferior adherence to antiretroviral therapy (ART) among HIV-positive patients. Given the limited body of work on this issue, we aimed to explore the relations between cigarette smoking, nicotine dependence, and ART adherence in Vietnam. A cross-sectional study of 1050 HIV-positive people was conducted from January to September 2013 in Hanoi (the capital) and Nam Dinh (a rural city). Adherence to ART during the last 30 days was measured by the 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
(25 reference statements)
1
21
0
Order By: Relevance
“…However, in multivariable models after adjusting for covariates, no significant associations were found between current smoking and imperfect ART adherence. Others (21, 22) have examined medication adherence and smoking in PLWH, and also have not found an association with ART adherence. It is possible that smoking and imperfect ART adherence share similar risk factors and, perhaps, smoking may be acting as a surrogate marker for these other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in multivariable models after adjusting for covariates, no significant associations were found between current smoking and imperfect ART adherence. Others (21, 22) have examined medication adherence and smoking in PLWH, and also have not found an association with ART adherence. It is possible that smoking and imperfect ART adherence share similar risk factors and, perhaps, smoking may be acting as a surrogate marker for these other factors.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have shown that smokers have a higher prevalence of detectable HIV viral load (14, 1820), overall, research in this area has provided mixed results with regard to the association between cigarette smoking and ART adherence. For example, two studies found no association between smoking status and ART adherence (21, 22), while another found that nicotine dependence (measured by the Fagerstrom Test for Nicotine Dependence [FTND]) was significantly related to suboptimal adherence (23). Thus, there remain open questions about the associations between smoking and HIV medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…This increased susceptibility has been mainly attributed to biochemical mechanisms including the immunosuppressive effects of smoking and its negative impact on immune and virological response even when on ART 13 . Behavioural mechanisms have also been suggested—for example, an association between smoking and non-adherence to antiretroviral therapy 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…Higher pre-ART CD4 levels among females and higher CD4 recovery among females compared to males has been reported elsewhere, thought to be partially due to later male access to HIV services and poorer male ART adherence [40][41][42][43]. To the best of our knowledge, however, the potential joint effect of male gender and anti-HCV-positive status has not been previously reported.…”
Section: Discussionmentioning
confidence: 38%
“…To reduce bias, the current analysis specifically adjusted for gender differences in baseline CD4 levels but did not adjust for other gender-related behaviors such as cigarette smoking and alcohol consumption which are more prevalent among HIV-infected males than HIV-infected females [40,41], and found to be associated with poorer ART adherence [42,43]. However, we cannot explain why anti-HCV-positive males and females had higher baseline CD4 levels than the other serogroups.…”
Section: Discussionmentioning
confidence: 99%